Discovering a novel therapy for disorders that feature defects of the neuromuscular junction structure - Panea, MD (2020)
Background: Congenital myasthenic syndromes (CMS) are a group of inherited disorders that affect signal transmission at the neuromuscular junction (NMJ) and share the clinical feature of fatigable muscle weakness. Downstream of tyrosine kinase 7 (DOK7) is a cytoplasmic-adaptor protein that amplifies the signalling from the muscle-specific receptor tyrosine kinase (MuSK), which is responsible for the formation and stabilisation of the NMJ. It has recently been shown that overexpression of DOK7 protein in muscles, generates enlarged NMJs in mice, which are very efficient in signal transmission, have no reported detrimental effects and can ultimately lead to a complete recovery for disease model mice. Aim: To study novel therapies for CMS based on DOK7 overexpression. Results: By using an adeno-associated virus system (DOK-AAV) we generated enlarged NMJs in wild-type mice to further investigate the morphology and electrophysiology of these synapses. The DOK7-AAV gene therapy was shown to generate enlarged synapses that improved the phenotype of two animal models of CMS. In addition, 5431 small molecules from a library of muscle-specific compounds were used in screening experiments to find potential small molecules that could upregulate DOK7. Confirmatory results were performed on an assay of biological activity and revealed two potential small molecule hits. They will provide the basis for a more detailed analysis of the effects of DOK7 upregulation in cell culture biological assays and ultimately for in vivo testing. Conclusion: These studies demonstrate that DOK7 upregulation would benefit differing CMS subtypes and could potentially improve signal transmission in other NMJ-associated disorders.